Manfred Kochen y Karl W. Deutsch, Decentralization, Sketches toward a Rational Theory, Publication of the Sciences Center Berlin, vol. 21, Oelgeschlager, Gunn & Hain Publishers, Inc., Cambridge, Mass, 1980, 356 pp. - Graizbord, Boris (Estudios Demográficos y Urbanos, 1984)
Manfred Kochen y Karl W. Deutsch, Decentralization, Sketches toward a Rational Theory, Publication of the Science Center Berlin, vol. 21, Oelgeschlager, Gunn & Hain, Publishers, Inc., Cambridge, Mass. 1980.